Cloning and Analysis of Holo-C-Phycocyanin Alpha Subunit Synthesis Genes from Nostoc spp. and Thermosynechococcus sp. TUBT-T01 - Sritusnee, Wipawee; Charoenrat, Theppanya; Chittapun, Supenya; Jaikaew, Phuphiphat; Dedvisitsakul, Plaipol; Piyapittayanun, Chanitchote (Burapha Science Journal, 2026)
C-phycocyanin is a blue-colored protein used as a fluorescent reagent for immunological analysis and natural pigment in food and cosmetics. Furthermore, many studies reported the pharmaceutical potential of C-phycocyanin due to its antioxidant properties. This study was conducted to isolate and clone the necessary genes for the synthesis of holo-C-phycocyanin alpha subunit including hox1 and pcyA from Nostoc spp. as well as cpcE and cpcF from Thermosynechococcus sp. TUBT-T01. The genes were successfully identified, cloned, and sequenced. Physiochemical properties and secondary structure of proteins were analyzed and predicted. The nucleotide sequences of each gene were aligned with those of other cyanobacterial strains available in the GenBank. The results indicated that the nucleotide sequences of hox1 from Nostoc sp. TUBT04 and pcyA from Nostoc sp. TUBT01 had 97% and 96% identity to those from Nostoc sp. NIES-4103 respectively. While the nucleotide sequences of cpcE and cpcF from Thermosynechococcus sp. TUBT-T01 had 90-92% identity to those from Thermosynechococcus sp. CL-1, Thermosynechococcus elongatus PKUAC-SCTE542, Thermosynechococcus vulcanus NIES-2134, and Thermosynechococcus elongatus BP-1. Results obtained from this study will be very beneficial for the production of holo-C-phycocyanin from Thermosynechococcus sp. TUBT-T01 using Escherichia coli expression system in the near future.